2011
DOI: 10.1039/c1ee01406d
|View full text |Cite
|
Sign up to set email alerts
|

Optimized thermoelectric properties of Mo3Sb7−xTex with significant phonon scattering by electrons

Abstract: Heavily doped compounds Mo 3 Sb 7Àx Te x (x ¼ 0, 1.0, 1.4, 1.8) were synthesized by solid state reaction and sintered by spark plasma sintering. Both X-ray diffraction and electron probe microanalysis indicated the maximum solubility of Te was around x ¼ 1.8. The trends in the electrical transport properties can generally be understood using a single parabolic band model, which predicts that the extremely high carrier concentration of Mo 3 Sb 7 ($10 22 cm À3 ) can be reduced to a nearly optimized level ($2 Â 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
53
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 40 publications
7
53
0
Order By: Relevance
“…Experimentally, the noticeable influence of electron-phonon interaction has been pointed out in some heavily doped TE materials, such as SiGe 158 and Mo 3 Se 7 . 159 When going beyond the conventional solids, the above mentioned small-perturbative methods have already become questionable or even invalid. The current implementation consists of introducing a phenomenological resonant scattering term as shown in equation (11) and treating it as another resistive scattering process.…”
Section: From the Conventional Phonon-phonon Interactions To Nanostrumentioning
confidence: 99%
“…Experimentally, the noticeable influence of electron-phonon interaction has been pointed out in some heavily doped TE materials, such as SiGe 158 and Mo 3 Se 7 . 159 When going beyond the conventional solids, the above mentioned small-perturbative methods have already become questionable or even invalid. The current implementation consists of introducing a phenomenological resonant scattering term as shown in equation (11) and treating it as another resistive scattering process.…”
Section: From the Conventional Phonon-phonon Interactions To Nanostrumentioning
confidence: 99%
“…Systems with sharp structures in their electronic density of states (DOS) near the Fermi level can be particularly sensitive to thermal excitation of phonons, as well as alloying effects [33][34][35] . This leads to adiabatic electron-phonon coupling effects which are important in the context of thermoelectric properties [35][36][37] , and which can influence the thermodynamics of the system 38 . The thermal atomic motions (phonons) in FeSi cause a strong renormalization of the electronic structure, filling the gap 19,23 , which in turn leads to anomalies in the temperature dependence of phonons 23 .…”
Section: Introductionmentioning
confidence: 99%
“…16 and 18) and YbCd 2Àx Zn x Sb 2 , both of which have zT values above unity at high temperatures. 11,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Recently, Yb 9 Mn 4.2 Sb 9 was shown to have promising thermoelectric performance (zT ¼ 0.7 at 950 K) by Bux et al 17 The structure of Yb 9 M 4+x Sb 9 is shown in Fig. 1, where M can be Fig.…”
Section: Introductionmentioning
confidence: 99%